2017
DOI: 10.4314/ahs.v17i3.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intimate partner violence on birth outcomes

Abstract: BackgroundViolence by intimate partner during pregnancy has many adverse pregnancy outcomes. Thus, that's why we sought to determine association between intimate partner violence during pregnancy and adverse birth outcomes.MethodsA facility based cross-sectional study was conducted among 183 recently delivered women from March 31–April 30, 2014 in public health facilities of Hossana Town. The data were collected through structured questionnaire and record review. Women who were not mentally and physically capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 24 publications
9
48
2
5
Order By: Relevance
“…The effects of IPV on PTB were examined by three studies. Of three, two studies found positive association between IPV and PTB [35,53] and one found no association [58]. Women exposed to IPV (AOR 2.5; 95% CI: 2.19-2.96) and physical violence (AOR 5.3; 95% CI: 3.95-7.09) during pregnancy were more likely to experience PTB [53].…”
Section: Sensitivity Analysesmentioning
confidence: 93%
See 1 more Smart Citation
“…The effects of IPV on PTB were examined by three studies. Of three, two studies found positive association between IPV and PTB [35,53] and one found no association [58]. Women exposed to IPV (AOR 2.5; 95% CI: 2.19-2.96) and physical violence (AOR 5.3; 95% CI: 3.95-7.09) during pregnancy were more likely to experience PTB [53].…”
Section: Sensitivity Analysesmentioning
confidence: 93%
“…, 11 from Ethiopia[52][53][54][55][56][57][58][59][60][61][62][63], 6 from Kenya[5,54,[64][65][66][67], 7 from Malawi [4, 6, 68-72], 3 from Sudan [10, 73, 74], 3 from Zambia [75-77],3 from Zimbabwe [78-80], 2 from Uganda [7, 81], 2 from Mozambique[82,83], 1 from Rwanda[84], and 1 from Madagascar[85]. Twenty five studies were done by cohort study design[33, 35, 36, 39, 41, 43, 45-50, 59, 61, 65-68, 70, 75, 77, 80, 83-85], 9 studies by case control study design[7,10,37,38,53,55,57,73,79] and 24 studies by cross sectional study design[4-6, 34, 40, 42, 44, 51, 52, 54, 56, 58, 60, 62, 64, 69, 71, 72, 74, 76, 78, 81, 82] (Table 1).…”
mentioning
confidence: 99%
“…A study from Dhanusha shows that 29 percent of the pregnant mother had faced at least one types of IPV during their pregnancy (22). Similarly, another study by Laelago, Belachew, and Tamrat (2017) observed that about 23 percent of the women had faced IPV during their pregnancy at Ethiopia. So it can be concluded that nearly one fourth of the mother are facing IPV during their pregnancy.…”
Section: Main Findingsmentioning
confidence: 99%
“…A study from Ethiopia shows that low birth weight and pre-term birth were associated with IPV (23,26). So, IPV not only influences the mother but also affects birth outcomes too.…”
Section: Main Findingsmentioning
confidence: 99%
“…Studies show that, birth asphyxia is related to severe disability such as low cognitive function, neurological problem and subtle cognitive impairment [9,10]. Although some studies demonstrated an association between IPV during pregnancy and birth asphyxia [11], others reported no association [12].…”
Section: Introductionmentioning
confidence: 99%